Распознавание фрагментов генов в ДНК - Андрейчук, И.И. (Компьютерная математика, 2011)
На основе аппарата цепей Маркова и байесовских процедур проведено распознавание известных экзонно-интронных фрагментов генов организма Caenorhabditis elegans. За допомогою апарата ланцюгів Маркова та байєсівських процедур проведено розпізнання відомих інтронно-екзонних фрагментів генів організму Caenorhabditis Elegans. On the basis of instrument of Bayesian approach and Markov chain, recognition procedure for gene fragments is obtained. The procedure has high percentage of recognition (80–90 %) and is simple and effective in computation. Its applicability is described by using Markov chains of 1-th order for the entire array of intron-exon sequences of the genome of a Caenorhabditis Elegans organism.